The Effectiveness of Online Learning on Motivation to Learn Physical Education: Evidence from East Lombok Junior High Schools - Jusran Jusran; Kurnia Taufik (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2025)
This study investigated the effectiveness of online learning on students’ learning motivation in Physical Education, Sports, and Health (PJOK) among eighth-grade students at SMP Islam NW Gayu during the COVID-19 pandemic. Employing a quantitative case study design, data were collected through validated questionnaires based on the Academic Motivation Scale (AMS), semi-structured interviews, and documentation. The sample consisted of 25 students with access to digital devices, selected purposively from a population of 48. Descriptive statistical analysis was used to determine the effectiveness levels of intrinsic and extrinsic motivation indicators. Results showed that online learning was moderately effective (52%) in sustaining students’ motivation, with extrinsic motivation (56%) higher than intrinsic motivation (48%). Family support, teacher feedback, and peer interaction were identified as the main drivers of engagement. However, limited autonomy, technological barriers, and reduced social connectedness hindered intrinsic motivation and active participation. Emotional comfort and competence-related factors, such as self-efficacy in using digital tools, also influenced students’ engagement. The findings align with Self-Determination Theory (SDT), suggesting that online physical education can foster learning motivation when autonomy, competence, and relatedness needs are fulfilled. Integrating hybrid learning, autonomy-supportive pedagogy, and continuous teacher development is recommended to enhance motivation and engagement in future online and blended PE programs